Improving Teacher Performance Management in Vocational High Schools in Producing Excellent Graduates - Ekka Suryapriadi, Yudi; Suwarni; Deisye Supit; Sugiharto (LPPM Undiksha, 2025)
This study examines the effectiveness of teacher performance management in vocational high schools in producing superior graduates. The problem raised is the low ability of students to compete in the world of work, which indicates the need for better management strategies. The urgency of this study lies in the importance of understanding the factors that influence teacher performance and the strategic position of schools in improving student competitiveness. The purpose of the study was to examine indicators of positional advantage and their impact on institutional performance in vocational high schools. The research method used was a survey with a sample of 457 vocational high school teachers in West Java Province. Data collection techniques were carried out through questionnaires designed based on relevant indicators, using a Likert scale to measure key variables such as teacher performance and industry support. Data analysis was carried out using Partial Least Square Structural Equation Modeling (PLS-SEM) to evaluate the relationship between variables. The results showed that positional advantage had a significant effect on institutional performance, with factors such as industry support and education management contributing positively. This finding confirms the importance of developing an integrated management strategy to improve teacher performance. The conclusion of this study is that strengthening the strategic position of schools can improve student competitiveness. The implications of this study provide insight for education managers and stakeholders in formulating policies that support improving the quality of education in Vocational High Schools, so that graduates can be better prepared to face challenges in the world of work.